2017
DOI: 10.1016/j.cmet.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Brown Fat-Derived Exosomes: Small Vesicles with Big Impact

Abstract: Adipose tissue (AT) not only stores energy, but also secretes hormones and releases small vesicles known as exosomes. Thomou et al. (2017) now show that exosomes secreted by brown fat carry miRNAs that regulate the liver. Thus, AT exosomes might have therapeutic and diagnostic relevance for metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…miRNAs can directly interact with complementary regions in the 3′ untranslated region of target mRNAs, thereby regulating their rate of promoting their degradation . In addition to functioning within cells, miRNAs have also recently been shown to be secreted extracellularly in exosomes, allowing for their transfer to proximal or distal cells where they can regulate gene expression . One recent study found that exosomes from patients with type 2 diabetes exhibit elevated levels of miR‐20b‐5p and that this miRNA impairs insulin activity within skeletal muscle .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can directly interact with complementary regions in the 3′ untranslated region of target mRNAs, thereby regulating their rate of promoting their degradation . In addition to functioning within cells, miRNAs have also recently been shown to be secreted extracellularly in exosomes, allowing for their transfer to proximal or distal cells where they can regulate gene expression . One recent study found that exosomes from patients with type 2 diabetes exhibit elevated levels of miR‐20b‐5p and that this miRNA impairs insulin activity within skeletal muscle .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are membrane‐bound phospholipid vesicles (40–150 nm in diameter) of endocytic origin (Chen, & Pfeifer, 2017; Guo, Tao et al., 2016; Im et al., 2014). Exosomes are intracellularly secreted by endocytic invagination of mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many researchers became interested in treating obesity and diabetes by activating brown adipose tissues or beige adipoctyes (28). Brown adipose tissues are also known to release EVs, which could be biomarkers of brown adipose tissue activity and therapeutic agents for obesity and related diseases (29).…”
Section: Introductionmentioning
confidence: 99%